Diazepam or midazolam for orotracheal intubation in the ICU? - Gehrke,Lísia (2015)
Objective: to compare clinical and cost effectiveness of midazolam and diazepam for urgent intubation. Methods: patients admitted to the Central ICU of the Santa Casa Hospital Complex in Porto Alegre, over the age of 18 years, undergoing urgent intubation during 6 months were eligible. Patients were randomized in a single-blinded manner to either intravenous diazepam or midazolam. Diazepam was given as a 5 mg intravenous bolus followed by aliquots of 5 mg each minute. Midazolam was given as an intravenous bolus of 5 mg with further aliquots of 2.5 mg each minute. Ramsay sedation scale 5-6 was considered adequate sedation. We recorded time and required doses to reach adequate sedation and duration of sedation. Results: thirty four patients were randomized, but one patient in the diazepam group was excluded because data were lost. Both groups were similar in terms of illness severity and demographics. Time for adequate sedation was shorter (132 ± 87 sec vs. 224 ± 117 sec, p = 0.016) but duration of sedation was similar (86 ± 67 min vs. 88 ± 50 min, p = 0.936) for diazepam in comparison to midazolam. Total drug dose to reach adequate sedation after either drugs was similar (10.0 [10.0-12.5] mg vs. 15.0 [10.0-17.5] mg, p = 0.248). Arterial pressure and sedation intensity reduced similarly overtime with both drugs. Cost of sedation was lower for diazepam than for midazolam (1.4[1.4-1.8] vs. 13.9[9.4-16.2] reais, p <0.001). Conclusions: intubation using intravenous diazepam and midazolam is effective and well tolerated. Sedation with diazepam is associated to a quicker sedation time and to lower costs.